A virtual breakthrough series collaborative to support deprescribing interventions across Veterans Affairs healthcare settings. - Phillips, Kristin K.; Mecca, Marcia C.; Baim‐Lance, Abigail M.; Schiller, Gabrielle S.; Pruskowski, Jennifer A.; Ellis, Elizabeth C.; Aponte‐Rosario, Deylen S.; Federovich‐Hogan, Amanda L.; Kossifologos, Annette C.; Martinez, Erica D.; Boockvar, Kenneth S. (Journal of the American Geriatrics Society, 2023)
Background: Virtual collaborative models are a practical way to implement a supportive environment for multi‐team learning. In this project, we aimed to describe the processes and outcomes of a virtual deprescribing collaborative that facilitated implementation of deprescribing interventions around the country. Methods: Two successive cohorts comprised of multidisciplinary teams from geographically diverse veterans affairs (VA) sites were selected via an application process to participate in a virtual deprescribing collaborative. Each site developed its own deprescribing protocol and took part in regular meetings, mentoring groups, monthly data reporting, and other learning activities over an approximate 9 month period, per cohort. Standard measures were number of veterans served and medications deprescribed. Descriptive and qualitative analyses were utilized. Results: Twenty‐one total VA sites were selected to participate in the deprescribing collaborative in two cohorts (Cohort 1, n = 12 sites; Cohort 2, n = 9 sites). The majority of sites' practice areas directly served the older adult population, and the majority of site leads were pharmacists. The most utilized tool used by the collaborative sites was the VA VIONE decision support tool (n = 14) and the most common strategy was individualized medication review. Combining outcomes from both Cohorts 1 and 2, a total of n = 4770 veterans were served, with 8332 medications deprescribed. Eighty‐two percent of Cohort 1 sites surveyed reported their deprescribing program was still being utilized after 1 year follow up. Conclusions: This virtual deprescribing collaborative aided in the successful implementation of both established and novel deprescribing practices across a variety of VA practice sites that care for older adults. The shared learning experience enhanced problem solving and allowed for interdisciplinary teamwork. Overall the collaborative was successful in improving polypharmacy for several thousand older adults.